Novel breath-hold liver target stereotactic ablative radiotherapy using the intrafraction diaphragm registration of kilovoltage projection streaming image with digitally reconstructed radiography of the planning computed tomography - Atsuto Katano; Yuki Nozawa; Masanari Minamitani; Hideomi Yamashita; Keiichi Nakagawa (Technical Innovations & Patient Support in Radiation Oncology, 2023)
Stereotactic ablative radiotherapy (SABR) is an emerging treatment option for patients with primary or metastatic liver tumors, particularly for those who are not eligible for surgery or transplantation. SABR is a high-precision radiation therapy that delivers a high dose of radiation to the tumor while minimizing the dose to the surrounding healthy tissues. However, the accurate targeting of the tumor is a crucial aspect of liver SABR, which requires real-time imaging and tracking of the liver and tumor motion during treatment. One of the motion management strategies for liver SABR is the repeated breath-hold technique, which involves the patient holding their breath multiple times during treatment delivery to reduce the movement of the liver and other organs due to breathing. This technique helps to improve the accuracy of the treatment and reduce the radiation dose to the healthy liver.The current study proposes a novel approach for multiple breath-hold volumetric modulated arc therapy (VMAT) stereotactic ablative radiotherapy for liver tumors, which uses the intrafraction diaphragm registration in real time to improve the accuracy and precision of the treatment. The proposed approach is based on real-time comparison of the diaphragmatic surface location between the digitally reconstructed radiography (DRR) and intrafraction kilovoltage projection streaming images (kV-PSI) having the same beam angles. The image cross-correlation between the DRR and the intrafraction kV-PSI provides a measure of the similarity between the two images and can be used to identify and track the diaphragm position during VMAT delivery. The proposed methodology consists of several steps, including planning CT and treatment planning, reference image reconstruction, and patient positioning and immobilization. The proposed approach has the potential to improve the accuracy and precision of liver cancer VMAT SABR, thereby increasing the efficacy of the treatment and reducing the risk of radiation exposure to surrounding healthy tissues.